Parents' perceived vulnerability and perceived control in preventing Meningococcal C infection: a large-scale interview study about vaccination - van der Wal Gerrit; Hirasing Remy A; Henneman Lidewij; Timmermans Danielle RM (BMC, 2008)
Abstract Background Parents' reported ambivalence toward large-scale vaccination programs for childhood diseases may be related to their perception of the risks of side-effects or safety of vaccination and the risk of contracting the disease. The aim of this study is to evaluate parents' perceptions of their child's risk contracting a Meningococcal C infection and parents' perceived control in preventing infection in relation to their evaluation of the safety, effectiveness and usefulness of vaccination. Methods In a large-scale interview study, a random sample of parents was interviewed after their children had received vaccination against Meningococcal C in a catch-up campaign. Questions were asked about the perceived relative vulnerability of their child contracting an infection, perceived control in preventing an infection, and parents' evaluation of the safety, usefulness and effectiveness of vaccination. Results 61% of 2910 (N = 1763) parents who were approached participated. A higher perceived relative vulnerability of their own child contracting the disease was related to a more positive evaluation of the vaccination campaign, while a lower perceived vulnerability did not result in a more negative evaluation. A higher perceived control in being able to prevent an infection was, however, related to a more critical attitude toward the safety, usefulness and effectiveness of vaccination. Conclusion Perceived relative vulnerability contracting an infection and parents' perceived control in preventing an infection seem to influence parents' evaluation of the vaccination programme. Future studies should determine if, and under which circumstances, these perceptions also affect parents' vaccination behaviour and would be relevant to be taken into account when educating parents about vaccination.